THE DESIGN OF TBECC (TEST OF BUSINESS ENGLISH COMMUNICATION COMPETENCE) FOR FRONT OFFICE STAFF IN HOTEL INDUSTRY: A CASE STUDY OF HOTELS IN SURABAYA, INDONESIA - Datu, Yerly A; Limantara, Singgih Widodo; Soelistiyowati, Endang; Hardjanto, Tofan Dwi; Fuadi, Yusron (PEOPLE: International Journal of Social Sciences, 2019)
Competition among hospitality industries in Indonesia has come to inevitable battle and, therefore, they must strengthen their front-liner staff for exemplary service due to the fact of the increasing numbers of hotels every year particularly in Surabaya, the capital of East Java Province and its role both for tourism and business. The role resulted in wave of expatriates coming to Surabaya and therefore strong English communication is considered important. Initial survey showed that specific English test for Front Office (FO) staff recruitment in hotels did not exactly exist. For this purpose, a qualitative research employing a case study approach was conducted. The research involved 8 hotels in Surabaya and 40 participants comprising hotel leaders and FO staff. The important stages were conducted such as conducting Focus Group Discussion (FGD) with hotel leaders, distributing a set of questionnaire to Front Office leaders and staff, as well as enhancing clarity and confirmation through interviews. From those stages, the writer formulated the Target Language Use (TLU) of Front Office Division as basis to construct the Test of Business English Communication Competence (TBECC). Results showed that at least 18 of 26 items were extracted as TLUs for speaking and 7 of 10 items were extracted to serve as TLUs for writing. Finally, based on the obtained TLUs, 14 questions for speaking were constructed and for writing test, 5 questions measured competencies such as filling a guest detailed form, writing a confirmation letter, welcome letter and email of coordination, as well as replying a complaint and writing a thank you email to guests. Finally, recommendation to involve more hotels that receive a huge number of foreigners as their guests was also given.